2019
DOI: 10.1155/2019/2672075
|View full text |Cite
|
Sign up to set email alerts
|

Trait Impulsivity Is Independent of Mild Cognitive Impairment in a Parkinson’s Disease Cohort

Abstract: Introduction Patients with Parkinson's disease (PD) commonly experience cognitive deficits and some also develop impulse control disorders (ICDs); however, the relationship between impulsivity and cognitive dysfunction remains unclear. This study investigated whether trait impulsivity associates with mild cognitive impairment (MCI), or is altered in a PD patient cohort with MCI. Methods A total of 302 patients with idiopathic PD were recruited sequentially from three Australian Movement Disorder clinics. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The clinical severity of this trait is also contextualized by comparison with other samples. BIS‐brief scores in JME were higher than in cohorts at risk of psychopathology, 30,32 and BIS‐11 scores were higher than PD 37,38 and OCD samples, 39 overlapped with anxiety and personality disorder samples 34,40 and lower than mood and schizophrenia spectrum disorder 35,40,41 and ADHD samples 35,36,41 . This extends findings from smaller, uncontrolled studies of trait impulsivity in JME using the BIS‐11 12 and the Temperament and Character Inventory, 10,13 and provides robust evidence for associations across multiple dimensions of impulsivity, including response and choice impulsivity 5,9,14 .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The clinical severity of this trait is also contextualized by comparison with other samples. BIS‐brief scores in JME were higher than in cohorts at risk of psychopathology, 30,32 and BIS‐11 scores were higher than PD 37,38 and OCD samples, 39 overlapped with anxiety and personality disorder samples 34,40 and lower than mood and schizophrenia spectrum disorder 35,40,41 and ADHD samples 35,36,41 . This extends findings from smaller, uncontrolled studies of trait impulsivity in JME using the BIS‐11 12 and the Temperament and Character Inventory, 10,13 and provides robust evidence for associations across multiple dimensions of impulsivity, including response and choice impulsivity 5,9,14 .…”
Section: Discussionsupporting
confidence: 65%
“…There was no difference between BIS‐brief score (p = 0.39), age (p = 0.56) or gender (p = 0.27) in this subset of individuals compared to the full JME cohort. The mean JME BIS‐11 score was 64.9 ± 10.2, and therefore higher than control, 34‐36 Parkinson’s disease (PD) 37,38 and obsessive‐compulsive disorder (OCD), 39 coinciding with personality 40 and anxiety disorder, 34 and lower than ADHD, 35,36,41 schizophrenia 35 and mood disorder 41 cohorts (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…The association of impulsivity with cognitive dysfunction in PD remains controversial. Although some reports have suggested an association between frontal lobe dysfunction and impulsivity 45 , others have suggested that impulsivity is independent of the cognitive state 46,47 . The multifaceted nature of impulsivity may explain these contradictory results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, each participant was evaluated by a clinical psychologist and completed a suite of neuropsychological assessments. Cognition was assessed using the Addenbrooke's Cognitive Examination Revised (ACE-R), as previously described [ 13 , 23 ], a sensitive test of cognition that can be efficiently applied in a clinical or research setting [ 24 ]. Whether patients were taking levodopa and/or dopamine agonists was noted.…”
Section: Methodsmentioning
confidence: 99%
“…Whilst several studies have focused on identifying demographic risk factors for the onset of impulsivity and ICDs in PD [ 7 , 10 13 ], to date none have investigated serum markers as predictive or associated factors of impulsivity in PD. Previous research has suggested a relationship between PD and serum levels of ceruloplasmin, a multicopper ferroxidase enzyme required for cellular efflux of iron from the central nervous system (CNS) [ 14 ], but has not investigated the relationship with impulsivity.…”
Section: Introductionmentioning
confidence: 99%